PROPOSED MARKETING STRATEGY FOR LOGISTICS SERVICE PROVIDER (A CASE STUDY: PT. SEMBRANI MUKTI TRANS) (The Indonesian Journal of Business Administration, 2019)
Digitalization era affects the micro, small, and medium-size enterprises (MSMEs) and Small Medium-sized Enterprises (SMEs) conducts the marketing and promotion via online media market place. Moreover, e-commerce is also growing. It generates the higher demand for logistics service provider in delivery process. The improvement and new innovation in technology generates more competitive advantage. Currently, PT. Sembrani Mukti Trans is still facing the issue that the sales growth is not increased while the market segment is increased that caused by lack of marketing strategy.This research uses quantitative descriptive method, which defined the current condition through the external analysis (PEST, Porter’s Five Force, and Competitor Analysis) and internal analysis (STP, Marketing Mix 7Ps, and Business Model Canvas). Followed with SWOT analysis and Root Cause Analysis) to define the market potential and root cause of the business issues. The main issues are caused by promotion, people, and product.There are several solutions after defining the TOWS Matrix and also supported by the research data from questionnaire that distributed into potential customer and interview the existing customer. To compete and gain more sales the company should provide digital marketing strategies, improve the skills and experinces of human resource, and develop new product.Keywords: Logistics Service Provider, TOWS Matrix, Marketing Mix, Business Model Canvas, Marketing Strategy.